Teachers and Urban‐Rural Gaps in Educational Outcomes. (11th April 2018) - Zhang, Jian; Jin, Songqing; Torero, Maximo; Li, Tao
Abstract: We examine the role of teachers in explaining the urban‐rural gap in educational outcomes. Using a large panel data set of students and teachers collected from China and explicitly controlling for the endogeneity of prior student academic achievement, we find that the urban‐rural difference in teacher effects contributes in large part to the observed urban‐rural gap in student academic achievement. In other words, if rural teachers were of the same quality as urban teachers, the urban‐rural gap in student academic achievement would be reduced substantially.